The effect of long-term fertilization on the 0.01 M CaCl2 extractable nutrient content of a meadow soil - Bertáné Szabó, Emese (Acta Agraria Debreceniensis, 2012)
During my research, I studied the 0.01 M CaCl2 extractable NO3--N, NH4+-N, Norg, P and K contents of the soil samples originated from a long term fertilisation trial in the experimental site Hajdúböszörmény. Relationships among the soil nutrient contents, the agronomic nutrient balances of the 2009 year, and fertilization were studied. From the results of the study it was concluded as follows:– Fertilization significantly increased the CaCl2 extractable NO3--N, NH4+-N, and K contents of soil.– Norg fraction increased as a function of the increasing yield. Hence, it can be assumed that the greater the produced yield, the more the stubble and root residues remain on the arable land. These organic residues can result significant increase in the Norg content of soils.– The CaCl2 extractable P and K contents were compared with the calculated P and K limit values. According to these, the experimental soil has a good phosphorus and lower potassium supply capacity. These results are in accordance with the results of the conventional Hungarian fertilization recommendation system.– It can be stated that the 0.01 M CaCl2 is able to determine not just inorganic N forms but Norg fraction as well that characterize the easily mineralizable nitrogen reserves. The results proved that AL-P and -K (ammonium lactate acetic acid, traditional Hungarian extractant) are in good agreement with the P and K reserves, but it is important from the aspect of environmental protection and plant nutrition to measure the easily soluble and exchangeable K-, and P-contents of soil. 0.01 M CaCl2 method is recommended for this.